Analisis Penggunaan Bahasa Gaul Remaja di RT 02 Simpang Tiga, Kecamatan Sungai Tebelian, Kabupaten Sintang, Provinsi Kalimantan Barat - Indira Zakya Putrie; Ari Wulandari (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
This study analyzes the phenomenon of slang language use among adolescents in RT 02 Simpang Tiga, Sungai Tebelian District, Sintang Regency. It aims to understand the social dynamics, technological advancements, and identity search reflected in their communication patterns. This descriptive qualitative research employed observation and in-depth interviews with adolescents aged 12-19 years as subjects. The findings reveal that slang serves as a primary communication tool for adolescents in their daily lives, including popular vocabulary such as "anjay," "bucin," "santuy," and "healing." Its use extends from social media to direct interactions with friends and family. Slang acts not only as a means of expression and intimacy but also as a marker of social status, participation in popular culture trends, and a tool for group solidarity. Dominant factors influencing its popularity include social media, peer groups, and popular culture (films, music, games). Interestingly, adolescents demonstrate good contextual awareness, differentiating between slang use in informal situations and formal Indonesian in official contexts. In terms of creativity, slang shows high linguistic innovation through wordplay, acronyms, and adaptations of foreign terms. Nevertheless, the extensive use of slang potentially impacts formal Indonesian language proficiency. Therefore, this study concludes the importance of a balanced understanding between appreciating adolescents' linguistic creativity and efforts to preserve good and correct Indonesian.